Mongolia : 2009 Article IV Consultation, Third Review Under Stand-by Arrangement, and Request for Modification of Performance Criteria; Staff Report; Staff Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Mongolia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This 2009 Article IV Consultation highlights that the global economic crisis and collapse in copper prices in 2008 hit the Mongolian economy hard. The loose macropolicies and tightly managed exchange rate pursued during the preceding boom years had made the economy particularly vulnerable, and the situation deteriorated markedly in early 2009. The authorities are making progress toward restoring health to public finances. Executive Directors have supported the authorities' policy priorities to restore health to public finances, rebuild international reserves while maintaining a flexible exchange rate, bolster confidence in the banking system, and protect the poor.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet